2016
DOI: 10.2139/ssrn.2734088
|View full text |Cite
|
Sign up to set email alerts
|

Models of Affective Decision-Making: How Do Feelings Predict Choice?

Abstract: Intuitively, how you feel about potential outcomes will determine your decisions. Indeed, an implicit assumption in one of the most influential theories in psychology, prospect theory, is that feelings govern choice. Surprisingly, however, very little is known about the rules by which feelings are transformed into decisions. Here, we specified a computational model that used feelings to predict choices. We found that this model predicted choice better than existing value-based models, showing a unique contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 18 publications
3
58
0
Order By: Relevance
“…People do not always overestimate in predicting and remembering emotion, however. Recent research reveals underestimation [26][27][28], and accuracy [12,29,30], as well as overestimation [31][32][33]. To account for this variation, Buechel, Zhang, and Morewedge [26] proposed that emotional experiences are more attention absorbing and richly detailed than forecasts.…”
Section: Similar Sources and Patterns Of Bias When Predicting And Remmentioning
confidence: 99%
“…People do not always overestimate in predicting and remembering emotion, however. Recent research reveals underestimation [26][27][28], and accuracy [12,29,30], as well as overestimation [31][32][33]. To account for this variation, Buechel, Zhang, and Morewedge [26] proposed that emotional experiences are more attention absorbing and richly detailed than forecasts.…”
Section: Similar Sources and Patterns Of Bias When Predicting And Remmentioning
confidence: 99%
“…Types of emotions are also referenced in empirical research. For example, attempts to reach a better understanding of the mechanisms of the emotional impact on decision making have incorporated different types of emotions into complex mediation models (Charpentier, De Neve, Li, Roiser, & Sharot, 2016;DeWall, Baumeister, Chester, & Bushman, 2016) and coherent types of emotion TYPES OF EMOTIONS 4 categorizations are useful in building more comprehensive models of human decision making (cf. Lerner et al, 2015, the EIC model).…”
mentioning
confidence: 99%
“…Further research, using computational modeling, has found that emotions experienced in response to gains and losses are better predictors of choices in a subsequent gambling task than the utility or objective value of an outcome (Charpentier, De Neve, Li, Roiser & Sharot, 2016). This relationship between past emotions and decisions suggesting that people may be using their past experiences to predict how they will feel in the future and, furthermore, those anticipated feelings seem to guide their behavior.…”
Section: The Importance Of Anticipated Emotions For Behaviormentioning
confidence: 99%
“…As reviewed above, anticipated emotions can cause changes in people's current emotional states, influence behavior, and motivate people to regulate their emotions in certain ways (Charpentier et al, 2016, Voelkle et al, 2013, Tamir, Mitchell & Gross, 2008. Additionally, as people age, they are likely to benefit more from earlier forms of emotion regulation that allow them to manage their emotions before they enter a situation (Charles, 2010;Livingstone & Isaacowitz, 2015;Sands & Isaacowitz, 2016;Voelkle et al, 2013).…”
Section: Current Researchmentioning
confidence: 99%
See 1 more Smart Citation